Analysis of Homestay Criteria Compliance in Tourist Village According to the Visitor's Perception - Franisal, Pusparani Nur (Jurnal Penelitian Pariwisata, 2020)
The development of tourism villages cannot be separated from the homestay existence as accommodation. As part of the tourism amenities, homestay's comfort is important. It's caused that the tourism activities products are intangible. Homestay feasibility will determine how long the visitor will allocate their time to stay in the tourist village. ASEAN Tourism in 2016 has published the standard homestay criteria, which contain nine variables standard criteria. The study aims to determine how far the homestay criteria' suitability in the tourism village according to visitors' perceptions in line with the ASEAN Tourism standard criteria established. Besides that, they also provide input to stakeholders to provide and manage the homestay properly and meet these criteria. This method is done by measuring six variables that are directly felt by visitors. The results show that among the six variables surveyed, five variables showed a level of conformity above 80%, and 1 variable in the level of 50% suitability. Keywords: criteria, tourist village, homestay